Investigation of the Relationship Between Socially Prescribed Perfectionism and Psychological Distress - Thomopoulos Aristeidis (2013)
Content, Abstract, Introduction, Rationale and Aim and Hypotheses, Methodology, Design, Participants, Materials, Procedure, Ethical Considerations, Data Analysis, Discussion, References, Appendices, PDF (Personal Development Plan)